Challenges in global reconstructive microsurgery: The sub-Saharan african surgeons' perspective. (June 2019) - Banda, Chihena H.; Georgios, Pafitanis; Narushima, Mitsunaga; Ishiura, Ryohei; Fujita, Minami; Goran, Jovic
Abstract: Background: Microsurgery is an essential element of plastic surgery practice. However, it remains unavailable or rudimentary in several developing countries, especially in sub-Saharan Africa. This study presents the local plastic surgeons experience, while focusing on specific challenges encountered and methods to improve the sub-Saharan global microsurgery practice. Methodology: An online survey was sent to all plastic surgeons registered with the College of Surgeons East Central and Southern Africa and respective national plastic surgical societies in the east central and southern Africa regional community. A total of 57 questionnaires were sent. Surgeons' country of practice, years of experience and rate of performing microsurgical procedures were considered. Results: The survey response rate was 56% ( n = 32). Most participants believed microsurgery was essential in the region. The leading challenge was inadequate perioperative care, mainly attributed to shortage of support staff ( n = 29, 91%). Others were lack of surgical expertise and resources. Interestingly, public unawareness of the benefits of microsurgery was also noted as a critical hindrance. The foremost suggestion on improvement ( n = 19, 59%) was to enhance training with a multidisciplinary team-building approach. Others included increased advocacy, publications and funding. Conclusion: The Plastic surgeons' perspective recognizes the needs of Global Reconstructive Microsurgery in sub-Saharan Africa. However, inadequate perioperative care, insufficient expertise, lack of equipment and lack of public awareness were major hindrances. Finally, there is a need to improve microsurgery in the region through advocacy, training and multidisciplinary team building.